2003
DOI: 10.4049/jimmunol.171.12.6690
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide LL-37 Activates Innate Immunity at the Airway Epithelial Surface by Transactivation of the Epidermal Growth Factor Receptor

Abstract: Antimicrobial peptides produced by epithelial cells and neutrophils represent essential elements of innate immunity, and include the defensin and cathelicidin family of antimicrobial polypeptides. The human cathelicidin cationic antimicrobial protein-18 is an antimicrobial peptide precursor predominantly expressed in neutrophils, and its active peptide LL-37 is released from the precursor through the action of neutrophil serine proteinases. LL-37 has been shown to display antimicrobial activity against a broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
343
6
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(374 citation statements)
references
References 47 publications
22
343
6
3
Order By: Relevance
“…Similarly, FPRL-1 expression was not seen in cultured keratinocytes or in whole skin by immunostaining. This result agrees with recent studies demonstrating that FPRL-1 is not involved in LL-37-induced activation of epithelial cells (21) or monocytes (23).…”
Section: Cathelicidin Peptide-induced Il-8 Production In Keratinocytesupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, FPRL-1 expression was not seen in cultured keratinocytes or in whole skin by immunostaining. This result agrees with recent studies demonstrating that FPRL-1 is not involved in LL-37-induced activation of epithelial cells (21) or monocytes (23).…”
Section: Cathelicidin Peptide-induced Il-8 Production In Keratinocytesupporting
confidence: 83%
“…The chemotactic property of LL-37 has been associated with binding via formyl peptide receptor-like 1 (FPRL-1) 2 (19), which belongs to the G i protein-coupled receptor family. Other host cell activities appear to be independent of FPRL-1 and can involve upstream activation of P2X7 or epidermal growth factor receptors (EGFR) (20,21).…”
mentioning
confidence: 99%
“…In a recent study, it was suggested that LL-37 activates airway epithelial cells by activation of the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK kinase ϭ MEK) via transactivation of the epidermal growth factor receptor (EGFR). 37 However, in our experiments, we did not detect any significant activation of ERK1/2.…”
Section: Discussioncontrasting
confidence: 68%
“…LL-37 also induces secretion of interleukin (IL)-8 in airway epithelial cells, leading to increased infiltration of neutrophils and amplification of inflammatory signal. The activation of epithelial cells has been suggested to be mediated through a sequential activation of molecular events, including induction of matrix metalloproteinases (MMP) activities, cleavage of membrane-anchored ligands of epidermal growth factor receptor (EGFR), and the subsequent transactivation of EGFR by these ligands [17] . In vivo study further suggests that this peptide stimulates macrophages to produce chemokines which in turn chemoattract additional cells to the inflamed sites [18] .…”
Section: Cathelicidin and Inflammationmentioning
confidence: 99%